2022
DOI: 10.3390/curroncol29060336
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence System for Predicting Prostate Cancer Lesions from Shear Wave Elastography Measurements

Abstract: (1) Objective: To design an artificial intelligence system for prostate cancer prediction using the data obtained by shear wave elastography of the prostate, by comparing it with the histopathological exam of the prostate biopsy specimens. (2) Material and methods: We have conducted a prospective study on 356 patients undergoing transrectal ultrasound-guided prostate biopsy, for suspicion of prostate cancer. All patients were examined using bi-dimensional shear wave ultrasonography, which was followed by stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The important aspect from human literature to be considered to implement sonoelastography in canine prostate evaluation is that both SE and 2D‐SWE have been proven to be highly sensitive not only to distinguish the healthy from diseased parenchyma but also to guide tissues biopsies, thus reducing the need for a systematic prostate sample and improve the accuracy of diagnosis, distinguish the lesions to be sampled with suspicion of malignancy from more benign lesions (Anbarasan et al, 2021; Kanagaraju et al, 2020; Secasan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The important aspect from human literature to be considered to implement sonoelastography in canine prostate evaluation is that both SE and 2D‐SWE have been proven to be highly sensitive not only to distinguish the healthy from diseased parenchyma but also to guide tissues biopsies, thus reducing the need for a systematic prostate sample and improve the accuracy of diagnosis, distinguish the lesions to be sampled with suspicion of malignancy from more benign lesions (Anbarasan et al, 2021; Kanagaraju et al, 2020; Secasan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the ever-growing arsenal of both biomarkers and modern multimodal imaging [ 17 ] has indeed greatly facilitated PC diagnosis, clinical staging, and risk stratification, as well as RP surgical planning. Specifically, mpMRI and targeted biopsies have revolutionized the diagnosis and management of PC.…”
Section: Pathogenesis Of Radical-prostatectomy-associated Morbiditymentioning
confidence: 99%
“…Cosmin Secasan et al [ 4 ] showed the results of their radiomics study on prostate cancer. Their experiments consisted of an AI system pipeline to predict malignant lesions from ultrasound (US) shear-wave elastography.…”
Section: Research and Clinical Topics Covered: Cancer Screening Diagn...mentioning
confidence: 99%